(untitled) (Experimental biology, 2016)
With the help window traps in SNNP "Ile-Alatau" were collected 864 specimens of insects belonging to 163 species, 142 genera, 63 families and 11 orders. Dominated by the number of representatives of four groups: Hymenoptera - 44,2%, Coleoptera - 23,0%, Hemiptera - 17,9%, Diptera - 11,8% of all instances. These 4 unit also has the greatest diversity of species. The share of the remaining units - only 3,0 %. The proportion of beetles - 58 species (52 kinds), bedbugs - 34 species (30 genera), Hymenoptera - 33 species (26 genera), Diptera - 24 species (20 genera). The greatest variety of sorts - in taxa with few species.